Blast Exposure Causes Long-Term Degeneration of Neuronal Cytoskeletal Elements in the Cochlear Nucleus: A Potential Mechanism for Chronic Auditory Dysfunctions - Arun, Peethambaran; Rossetti, Franco; Wilder, Donna M.; Wang, Ying; Gist, Irene D.; Long, Joseph B. (Frontiers in Neurology, 2021)
Blast-induced auditory dysfunctions including tinnitus are the most prevalent disabilities in the service members returning from recent combat operations. Most of the previous studies were focused on the effect of blast exposure on the peripheral auditory system and not much on the central auditory signal processing regions in the brain. In the current study, we have exposed rats to single and tightly coupled repeated blasts and examined degeneration of neuronal cytoskeletal elements using silver staining in the central auditory signal processing regions in the brain at 24 hr, 14 days, 1 month, 6 months and 1 year. The brain regions evaluated include cochlear nucleus, lateral lemniscus, inferior colliculus, medial geniculate nucleus and auditory cortex. The results obtained indicated that a significant increase in degeneration of neuronal cytoskeletal elements was observed only in the left and right cochlear nucleus. A significant increase in degeneration of neuronal cytoskeletal elements was observed in the cochlear nucleus at 24 hr and persisted through 1 year, suggesting acute and chronic neuronal degeneration after blast exposure. No statistically significant differences were observed between single and repeated blasts. The localized degeneration of neuronal cytoskeletal elements in the cochlear nucleus suggests that the damage could be caused by transmission of blast shockwaves/noise through the ear canal and that use of suitable ear protection devices can protect against acute and chronic central auditory signal processing defects including tinnitus after blast exposure.